A New Blow-Up Criterion for the DGH Equation - Mingxuan Zhu; Liangbing Jin; Zaihong Jiang (Abstract and Applied Analysis)
We investigate the DGH equation. Analogous to the Camassa-Holm equation, this equation possesses the blow-up phenomenon. We establish a new blow up criterion on the initial data to guarantee the formulation of singularities in finite time.